An Investigation on Low Velocity Impact Response of Multilayer Sandwich Composite Structures - S. Jedari Salami; M. Sadighi; M. Shakeri; M. Moeinfar (The Scientific World Journal)
The effects of adding an extra layer within a sandwich panel and two different core types in top and bottom cores on low velocity impact loadings are studied experimentally in this paper. The panel includes polymer composite laminated sheets for faces and the internal laminated sheet called extra layer sheet, and two types of crushable foams are selected as the core material. Low velocity impact tests were carried out by drop hammer testing machine to the clamped multilayer sandwich panels with expanded polypropylene (EPP) and polyurethane rigid (PUR) in the top and bottom cores. Local displacement of the top core, contact force and deflection of the sandwich panel were obtained for different locations of the internal sheet; meanwhile the EPP and PUR were used in the top and bottom cores alternatively. It was found that the core material type has made significant role in improving the sandwich panel’s behavior compared with the effect of extra layer location.